Respon Pertumbuhan dan Hasil Tanaman Jagung Manis terhadap Pemberian Dosis Limbah Industri Pengolahan Karet pada Tanah Podsolik - Khairullah Khairullah; Mahdiannoor; Norhasanah Norhasanah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Corn as a food ingredient ranks second after rice, besides it is also used as animal feed ingredients and industrial raw materials. Low productivity of corn due to varied soil fertility and not using superior varieties. To increase high yields, fertilization is needed, both chemical fertilizers and organic fertilizers such as podsolic soil. The purpose of this study (i) to determine the response of growth and yield of maize to the provision of rubber processing industry waste on podsolic soil (ii) get the best dose of rubber processing industry waste for the growth and yield of corn plants on podsolic soil. The study was conducted in the village of Haruyan Seberang RT 05 Rw 02 Kec. Haruyan Kab, Hulu Sungai Tengah, from April - June 2012, used a Randomized Block Design (RBD) with 5 treatments and 5 replications, so that there were 25 experimental units. The factors tested were the administration of several doses of rubber industry waste, namely (k0) without treatment, (k1) 10 t.ha-1 = 3.4 kg.plot-1, (k2) 20 t.ha-1 = 6.8 kg.plot-1, (k3) 30 t.ha-1 = 10.2 kg.plot-1 and (k4) 40 t.ha-1 = 13.6 kg.plot-1. The results showed the response of corn stalk diameter aged 21 and 28 DAP, number of leaves aged 14 DAP and length of corn cobs planted; there was no response of plant height aged 14, 21 and 28 DAP, stem diameter of 14 DAP, number of leaves aged 21 and 28 DAP and weight of ear of crop on treatment of dosing of rubber industry waste. The best dose of rubber processing industry waste for growth and yield of corn plants is 40 t.ha-1 (13.6 kg.plot-1).